Compare study cellulose/Mn3O4 composites using four types of alkalis by sonochemistry method. (22nd January 2015) - Fu, Lian-Hua; Li, Shu-Ming; Bian, Jing; Ma, Ming-Guo; Long, Xing-Luan; Zhang, Xue-Ming; Liu, Shi-Jie
Graphical abstract: Highlights: Cellulose/Mn3 O4 composites were fabricated via sonochemistry method. Mn3 O4 crystals were obtained by thermal treatment of cellulose/Mn3 O4 composites. Types of alkalis played an important role in the phase, shape, and thermal stability. Formation mechanism of cellulose-based composites were researched. Abstract: The purpose of this article was to explore the influences of alkalis types on the cellulose/Mn3 O4 composites via a sonochemistry method. In this study, cellulose/Mn3 O4 composites were successfully fabricated using four types of alkalis (urea (CO(NH2 )2 ), hexamethylenetetramine ((CH2 )6 N4, HMT), NaOH, and KOH) by an environmentally-friendly sonochemistry method. The phase, shape, thermal stability, and the formation mechanism of the cellulose composites were researched in detail. Experimental results demonstrated that the types of alkalis played an important role in the phase, shape, dispersion, and thermal stability of cellulose/Mn3 O4 composites. By thermal treatment of cellulose/Mn3 O4 composites at 600 °C for 3 h in air, the Mn3 O4 crystals were obtained. This novel method reported here maybe has a guiding significance for the synthesis of manganese oxide materials and other metal oxides using cellulose as template.